(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
The article talks about the importance of using fiction in teaching foreign languages. It is emphasized that it is the work with fiction that contributes to the familiarization with the national and cultural specifics of speech behavior in the country of the language being studied; helps to form students’ understanding of various spheres of modern life of another society, its history and culture.